2018
DOI: 10.1002/chem.201802269
|View full text |Cite
|
Sign up to set email alerts
|

Transition‐Metal‐Free N‐Arylation of Amines by Triarylsulfonium Triflates

Abstract: A simple and efficient method for transition-metal-free N-arylation of various amines by triarylsulfonium triflates is described. Both aliphatic and aromatic amines were smoothly converted at 80 °C in the presence of tBuOK or KOH to give the corresponding mono N-arylated products in good to high yields. The molar ratios of the reactants and the choice of bases had a big effect on the reaction. When a large excess of [Ph S][OTf] and tBuOK were employed for primary amines under the standard conditions, the bis(N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…In the previous alkali‐initiated decomposition of triarylsulfonium salts, three possible mechanisms have been documented in the literatures: a S N Ar mechanism, a benzyne intermediate, and a radical process. In our recent work, the aryne species have proved to be the major reactive intermediates in transition‐metal‐free N ‐arylation of amines by triarylsulfonium triflates in the presence of t BuOK or KOH . However, in this work the investigations revealed that the aryne intermediates might not be involved in the base‐mediated O‐arylation of alcohols and phenols by triarylsulfonium triflates.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…In the previous alkali‐initiated decomposition of triarylsulfonium salts, three possible mechanisms have been documented in the literatures: a S N Ar mechanism, a benzyne intermediate, and a radical process. In our recent work, the aryne species have proved to be the major reactive intermediates in transition‐metal‐free N ‐arylation of amines by triarylsulfonium triflates in the presence of t BuOK or KOH . However, in this work the investigations revealed that the aryne intermediates might not be involved in the base‐mediated O‐arylation of alcohols and phenols by triarylsulfonium triflates.…”
Section: Resultsmentioning
confidence: 75%
“…The less effective production of 3 u and 3 y in the presence of CsOH might be attributed to the relatively poorer acidity of the starting alcohols as well as their steric hindrance, which required stronger base such as NaH for the conversion. Since the free NH 2 groups could be arylated by [Ar 3 S][OTf] in the presence of bases, the reaction of ethanolamine ( 1 z ) with 2 a (1.5 or 3 equiv) and CsOH (1.5 or 3 equiv) under the standard conditions formed bis(arylated) product 3 z in 22 % or 56 % yield, respectively, accompanied by a trace amount or 19 % of tri(arylated) product ( N‐( 2‐phenoxyethyl)diphenylamine, 3 z′ ). Notably, when 1,3‐butanediol ( 1 aa ) reacted with 2 a /CsOH at 50 °C for 24 h, 4‐phenoxy‐2‐butanol ( 3 aa ) was formed in 88 % yield with the secondary hydroxyl group unchanged, suggesting that the O‐phenylation could selectively occur at the primary alcoholic‐OH site.…”
Section: Resultsmentioning
confidence: 99%
“…The transition‐metal‐catalyzed C−N bond formation, known as N‐arylation reaction, has attracted much attention in organic synthesis. It is one of the most useful methods for the construction of N‐aryl amines, which constitute important structural units in various biologically active pharmaceutical ingredients and natural products . The most promising method in the literature for the N‐arylation reaction is Copper‐catalyzed Ullmann‐type transformation.…”
Section: Introductionmentioning
confidence: 99%
“…Diphenylamine (DPA) is primarily used as astabilizer for nitrocellulose explosives [1] and the detection of oxidizers, [2] whereas C-alkylated diphenylamines are widely used as antioxidants for the preservation of fruits, [3] oils, [4] and polymers. In addition, other methods, including P III /P V =Oc atalysis, [15] iodine, [16] sulfonium triflates, [17] various nanoparticle catalysts, [18] and Pd/C catalysis for the formationo fa rylamines from aliphatic substrates, [19] have also been reported. [7] Additionally,t riphenylamines are important for the preparation of optoelectronic materials.…”
mentioning
confidence: 99%
“…[10] Arylamines are commonly prepared from amine precursors through metal-catalyzedC ÀNc oupling reactions. In addition, other methods, including P III /P V =Oc atalysis, [15] iodine, [16] sulfonium triflates, [17] various nanoparticle catalysts, [18] and Pd/C catalysis for the formationo fa rylamines from aliphatic substrates, [19] have also been reported. In addition, other methods, including P III /P V =Oc atalysis, [15] iodine, [16] sulfonium triflates, [17] various nanoparticle catalysts, [18] and Pd/C catalysis for the formationo fa rylamines from aliphatic substrates, [19] have also been reported.…”
mentioning
confidence: 99%